(untitled) (Research, Society and Development, 2020)
The final disposal of solid waste produced on a daily basis has become an obstacle, generating a source of several environmental impacts, favoring environmental degradation. To minimize these effects, there are some final disposal methods such as: dumps; landfills (controlled and sanitary); composting and recycling. However the most used in the Northeast region are the dumps, however, this method is the most aggressive to the environment. In this context, it is necessary to carry out a preliminary risk analysis and Checklist in order to predict how much residues can harm soil, water and air of a given locality, thus determining its risks and dangers. This research was based on the evaluation of the environmental damages diagnosed through the knowledge of the risks and dangers presented in the management of urban solid waste and in the dump. Initially a questionnaire was developed to be applied to garbage collectors responsible for selective collection of landfill and recycling cooperative of mentioned municipality. After the first step, data on the risks and dangers of these materials were quantified. Results obtained through the questionnaire responses confirmed that garbage collectors do not use all personal protective equipment and are exposed to risks and possible dangers. Quantification of level of average risk was critical and magnitude of dangers was average, values worrisome, but possible to be reversed.